Health-related behaviors among pregnant women with hypertension - Bień, Agnieszka Maria; Krysa, Justyna; Rzońca, Ewa; Iwanowicz-Palus, Grażyna; Mękal-Kisiel, Joanna (Journal of Education, Health and Sport, 2017)
Introduction. The healthy and unhealthy behaviors of a pregnant woman influence both her own health and that of her unborn child, affecting its future development. The purpose of the study was to evaluate the health-related behaviors of pregnant women with hypertension. Material i method. The study was performed between November 2011 and February 2012 and included 80 hypertensive pregnant women hospitalized in a high risk pregnancy ward. The study used a diagnostic survey with questionnaires. Results. Statistical analyses showed a correlation between the respondents’ health-related behaviors and their socio-demographic characteristics: exercise was correlated with age (p=0.01), and rest during the day was correlated with support in everyday responsibilities (p<0.00001), and with the respondents’ socio-economic standing (p=0.03). Correlations were also found between healthy eating habits and residence (0.006), education (p=0.05), and sodium intake (p=0.0003), as well as between education and substance use (p=0.0003). Conclusion. Health-related behaviors of pregnant women with hypertension are influenced by their education, support they receive in daily responsibilities, and their socio-economic standing. The diagnosis of hypertension in pregnant women does not necessarily prompt them to discontinue all unhealthy behaviors.